This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I can't solve it by Algebra but by Calculus using Lagrange multipliers and defining F ( x , y , z , λ ) = x y + 2 y z − λ ( x 2 + y 2 + z 2 − 3 6 ) . Then taking partial derivatives and equating them to zero.
∂ x ∂ F = y − 2 λ x ∂ y ∂ F = x + 2 z − 2 λ y ∂ z ∂ F = 2 y − 2 λ z ∂ λ ∂ F = − x 2 − y 2 − z 2 + 3 6 ⟹ x y = 2 λ ⟹ y x + 2 z = 2 λ ⟹ z 2 y = 2 λ ⟹ x 2 + y 2 + z 2 = 3 6
⟹ 2 λ = x y = y x + 2 z = z 2 y . From x y = z 2 y ⟹ z = 2 x .
From x y = y x + 2 z = y 5 x ⟹ y 2 = 5 x 2 . From x 2 + y 2 + z 2 = 3 6 ⟹ x 2 + 5 x 2 + 4 x 2 = 3 6
⟹ x = 1 0 6 , y = 3 2 , and z = 1 0 1 2 .
Therefore, max ( F ( x , y , z , 0 ) = F ( 1 0 6 , 3 2 , 1 0 1 2 , 0 ) = 1 0 6 ⋅ 3 2 + 2 ⋅ 3 2 ⋅ 1 0 1 2 = 1 8 5 ≈ 4 0 . 2